Volcanoes - Decker, Robert W. (Robert Wayne), 1927-; Decker, Barbara, 1929- (New York : W.H. Freeman, 1998)
Provides information about volcanology, discussing the science behind the natural disasters, with descriptions of some of the world's major volcanic eruptions, photographs, and a listing of Web sites carrying news of volcanic activitiy.
Includes bibliographical references and index.
Wilson's Senior High School.
Young Adult
Keywords: Volcanoes; Volcanoes